اثر جودة الخدمات الفندقية على ولاء العميل - طالبي أيوب; بوطيب عبد العالي (جامعة الوادي University Of Eloued, 2025)
تهدف هذه الدراسة إلى استكشاف العلاقة بين جودة الخدمات وولاء العميل في القطاع الفندقي، من خلال اختبار فرضيات تربط ولاء العميل بعدة أبعاد لجودة الخدمات، تشمل الاعتمادية، الملموسية، الاستجابة، الكفاءة، المجاملة، المصداقية، الأمان، والوصول. كما تهدف إلى تحديد الأبعاد التي تؤثر بشكل أكبر على ولاء العملاء، ودراسة الفروق بين عدد من الفنادق فيما يتعلق بجودة الخدمات وولاء العملاء. استخدمت الدراسة أساليب تحليلية مثل نماذج الانحدار البسيط والمتعدد، تحليل التباين (ANOVA)، واختبار Tukey HSD لمقارنة أداء الفنادق. أظهرت النتائج وجود علاقة إيجابية وقوية بين جودة الخدمات وولاء العميل، حيث تفسر جودة الخدمات حوالي 70% من التغير في ولاء العملاء. كانت أبعاد المصداقية، الاستجابة، الكفاءة، الأمان، والفهم هي الأبرز تأثيرًا، في حين كان لأبعاد الوصول، الملموسية، والاعتمادية تأثير أقل مع دلالة إحصائية. كما بينت نتائج تحليل الفروق وجود اختلافات ذات دلالة إحصائية في ولاء العملاء بين الفنادق، مع تفوق واضح لفندق ""نزل لوس"" يليه ""نزل سوف"". تشير الدراسة إلى ضرورة تعزيز جودة الخدمات مع التركيز على الأبعاد المؤثرة لتعزيز ولاء العملاء وتحسين تنافسية الفنادق. توصي بتطوير قدرات الاستجابة والكفاءة، وزيادة الأمان والمصداقية، وتحسين تجربة العميل في جميع مراحل التفاعل. تؤكد الدراسة أهمية جودة الخدمة كعامل رئيسي لاستدامة ولاء العملاء، مما ينعكس إيجابيًا على نمو القطاع الفندقي في ظل التحديات الحالية. "Abstract This study aims to explore the relationship between service quality and customer loyalty in the hospitality sector by testing hypotheses linking customer loyalty to several dimensions of service quality, including reliability, tangibility, responsiveness, competence, courtesy, credibility, security, and accessibility. It also seeks to identify the dimensions with the greatest impact on customer loyalty and to examine differences among several hotels in terms of service quality and customer loyalty. The study employed analytical methods such as simple and multiple regression models, analysis of variance (ANOVA), and the Tukey HSD test to compare hotel performance. Results showed a strong positive relationship between service quality and customer loyalty, with service quality explaining about 70% of the variance in customer loyalty. The dimensions of credibility, responsiveness, competence, security, and understanding had the most significant impact, while accessibility, tangibility, and reliability had a lesser but statistically significant effect. The variance analysis also revealed statistically significant differences in customer loyalty among hotels, with Hotel ""Nzel Lous"" clearly outperforming others, followed by Hotel ""Nzel Sof."" The study highlights the need to enhance service quality by focusing on the most influential dimensions to strengthen customer loyalty and improve hotel competitiveness. It recommends developing responsiveness and competence capabilities, increasing security and credibility, and improving the customer experience at all interaction stages. The study confirms that service quality is a key factor in sustaining customer loyalty, which positively affects the growth of the hospitality sector amid current challenges.
Keywords: جودة الخدمات; ولاء العميل، أبعاد جودة الخدمات الفندقية; تجربة العميل; Service quality; customer loyalty; service quality dimensions; customer experience.